AE energy evolution during CJB fracture affected by rock heterogeneity and column irregularity under lateral pressure. Issue 1 (31st December 2022) - Gong, Bin; Wang, Yongyi; Zhao, Tao; Tang, Chun'an; Yang, Xiaoyu; Chen, Tiantian
Abstract: Considering that the mechanical mechanism and energy release law of gradual failure of columnar jointed basalt (CJB) are affected by lateral pressure, rock heterogeneity and column irregularity, etc., the numerical CJB models with various column dip angles, irregularity degrees of column and lateral pressures were established through the digital image correlation. The progressive failure process and released energy of CJBs were simulated under the loading rate of 0.05 mm/ step based the continuum mechanics and statistical damage theory. The influences of rock inhomogeneity, column irregularity degree, and model boundary on the nonlinear deformation and failure of CJB were comprehensively investigated. The results demonstrate that the effect of the inhomogeneity index depends on column dip angle, and the equivalent deformation modulus of CJBs is more sensitive to the inhomogeneity index than the lateral pressure. Moreover, the compressive strength along the direction perpendicular to the column axis basically decreases with column irregularity degree increasing when the meso strength of rock is 120 MPa. Besides, the mechanical properties and elastic energy of irregular CJBs are greatly affected by the model boundaries. These achievements will contribute to understanding the inner failure mechanism and energy evolution of CJBs.